2006
DOI: 10.1080/15265160500394994
|View full text |Cite
|
Sign up to set email alerts
|

Deception, Catholicism, and Hope: Understanding Problems in the Communication of Unfavorable Prognoses in Traditionally-Catholic Countries

Abstract: The doctor's use of deception in appropriate circumstances has commonly been considered a necessity of the medical art. Resistance to full and frank communication is typical of many traditionally Catholic countries, and particularly of Italy, a western country where Catholicism remains particularly influential. The Catholic teaching on truth and lies, and the problem of telling the truth to a severely ill patient is discussed. It is suggested that the contemporary Catholic model of gradually telling a terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…This distinction between letting life go and taking life is not uncommon in cultures that place strong emphasis on the value of human life or the preservation of hope. 2,4,12 In this case, the shock function of the ICD did, indeed, serve the intention of the surrogate decision makers to prolong life, meeting what they saw as their religious obligationsduntil the patient suffered a type of arrest that could not be treated by an ICD shock, or until the ICD battery was exhausted. The family did not view ICD generator replacement in the same way.…”
Section: Icd Replacement and Deactivationmentioning
confidence: 86%
“…This distinction between letting life go and taking life is not uncommon in cultures that place strong emphasis on the value of human life or the preservation of hope. 2,4,12 In this case, the shock function of the ICD did, indeed, serve the intention of the surrogate decision makers to prolong life, meeting what they saw as their religious obligationsduntil the patient suffered a type of arrest that could not be treated by an ICD shock, or until the ICD battery was exhausted. The family did not view ICD generator replacement in the same way.…”
Section: Icd Replacement and Deactivationmentioning
confidence: 86%
“…Some previous studies discussed hope and deception. (Ruddick 1999, Toscani & Farsides 2006). It seemed that deception in appropriate circumstances was commonly considered a necessity of the medical art.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found, for instance, that discussions of end-of-life topics by general practitioners occur most often in the Netherlands and least often in Italy (Evans et al, 2014), which could indicate how common it is for healthcare providers discuss end-of-life matters with patients. Furthermore, in Mediterranean countries such as Italy healthcare providers often practice partial-or non-disclosure of end-of-life issues, due to wishes of family who are often involved in care (Gysels et al, 2012) and to the importance of maintaining patient's hope and not causing them distress (Toscani and Farsides, 2006).…”
mentioning
confidence: 99%